The factors that determine the successful entrepreneurs among 1azam receivers in Samarahan district, Kota Samarahan Sarawak. - Siti Rohaya Wahet (2017)
The implementation of program development is becoming the most important agenda for any of the government nowadays. These development programs are sustainable tools for the development of any nation in the world. The success and failure of any nation or any state is depending greatly on the development programs implemented by the government to sustain in this world. For this reason, the federal government is focusing in carrying out continuous development programs for sustainable development. To achieve this agenda, the government has launched a development program which is called as 1Azam program. This program is introduced in the year of 2010 with the main objective to reduce the poverty rate among Malaysians by providing employment and/or entrepreneurship to those Malaysians who were poor or extreme poor. Besides, this program also aimed to increase the income level of the society and to match with the right skills of the 1 AZAM participants in order for them to excel in their life. Factors that determines the successful entrepreneurs among 1AZAM recipients in Samarahan District is the main subject of this research. Respondents will be selected randomly for the study through questionnaires, in which every person of the population has a chance of being selected. The findings of this research demonstrate that some of the success factors have a significant relationship with the successful entrepreneurs among 1Azam recipients. Based on the analysis and findings in this research, it is found that family background and previous experience are the most determine factors in order to become successful entrepreneurs among 1AZAM recipients in Samarahan District.